TOI-530b: a giant planet transiting an M-dwarf detected by TESS. Issue 1 (22nd December 2021) - Gan, Tianjun; Lin, Zitao; Wang, Sharon Xuesong; Mao, Shude; Fouqué, Pascal; Fan, Jiahao; Bedell, Megan; Stassun, Keivan G; Giacalone, Steven; Fukui, Akihiko; Murgas, Felipe; Ciardi, David R; et al.
ABSTRACT: We report the discovery of TOI-530b, a transiting Saturn-like planet around an M0.5V dwarf, delivered by the Transiting Exoplanet Survey Satellite ( TESS ). The host star is located at a distance of 147.7 ± 0.6 pc with a radius of R * = 0.54 ± 0.03 R ⊙ and a mass of M * = 0.53 ± 0.02 M⊙ . We verify the planetary nature of the transit signals by combining ground-based multiwavelength photometry, high-resolution spectroscopy from SPIRou as well as high-angular-resolution imaging. With V = 15.4 mag, TOI-530b is orbiting one of the faintest stars accessible by ground-based spectroscopy. Our model reveals that TOI-530b has a radius of 0.83 ± 0.05 RJ and a mass of 0.37 ± 0.08 MJ on a 6.39-d orbit. TOI-530b is the sixth transiting giant planet hosted by an M-type star, which is predicted to be infrequent according to core accretion theory, making it a valuable object to further study the formation and migration history of similar planets. Furthermore, we identify a potential dearth of hot massive giant planets around M-dwarfs with separation distance smaller than 0.1 au and planet-to-star mass ratio between 2 × 10 −3 and 10 −2 . We also find a possible correlation between hot giant planet formation and the metallicity of its parent M-dwarf. We discuss the potential formation channel of such systems.